2020
DOI: 10.1016/j.msea.2020.139476
|View full text |Cite
|
Sign up to set email alerts
|

Self-heating behavior during cyclic loadings of 316L stainless steel specimens manufactured or repaired by Directed Energy Deposition

Abstract: The purpose of this article is to assess a self-heating testing method for the characterization of fatigue properties of single-track thickness additively manufactured specimens. It also evaluates the impact of the microstructure orientation with respect to the loading direction on the dissipative behavior and the initiation of microcracks. The 316L stainless steel specimens under scrutiny were manufactured by Directed Energy Deposition in two configurations: (i) fully printed specimens (2 orientations) and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…7 Process plan alternatives generated for the particular case study treatment. Although 316L cannot be heat treated, AM of 316L alloys has been successfully used in the past [32][33][34][35][36][37], even for repair purposes [38], and its fatigue life has been deemed satisfactory [39][40][41]. The processes used in this case are DLM, milling, and vision-based metrology, but additional processes could be considered as appropriate.…”
Section: Case Studymentioning
confidence: 99%
“…7 Process plan alternatives generated for the particular case study treatment. Although 316L cannot be heat treated, AM of 316L alloys has been successfully used in the past [32][33][34][35][36][37], even for repair purposes [38], and its fatigue life has been deemed satisfactory [39][40][41]. The processes used in this case are DLM, milling, and vision-based metrology, but additional processes could be considered as appropriate.…”
Section: Case Studymentioning
confidence: 99%
“…It has been observed that additively manufactured 316L exhibits higher yield stress and ultimate tensile strength than conventionally manufactured 316L, and a lower elongation to failure and fracture toughness [19]. In addition, the influence of layer orientation and surface roughness on the fatigue behavior of SLM parts were addressed in [20,21]. The ability to manufacture 316L stainless steel parts using the DED additive manufacturing technology have been investigated in a number of recent works [22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition to the fabrication of new parts, the WAAM technique also facilitates the repair of damaged structures, as an alternative to the replacement of the entire component. 6,7 Similarly to all AM techniques, as well as all the advantages mentioned for WAAM, this technique may also involve some disadvantages. The main disadvantage of such a fabrication method is the possibility of relatively high roughness on the outer surface of the as-built parts and dimensional inaccuracies that may impose the requirement of further post-deposition treatments such as surface machining, high pressure rolling, etc.…”
Section: Introductionmentioning
confidence: 99%